Electrode Reaction Kinetics at High Electrolyte Concentrations. H2 Oxidation and O2 Evolution in KOH - Paul Ruetschi (CHIMIA)
The kinetics of electrode reactions in concentrated electrolytes can be described with the usual rate equation provided that activities, rather than concentrations, of the reacting species are being used, that account is being taken of the activity of participating water molecules and that an activity coefficient of the activated complex estimated from the activity coefficient of reacting and/or resulting species, is being introduced.